Issues in the Hong Kong Applied Learning Trials (Asian Education Studies, 2018)
This paper presents critical issues in the conceptualisation and positioning of applied learning (APL) in Hong Kong trials. It draws on a critical review of official documentation and interviews with participants involved in the 2003-09 developmental trials of APL policy: policy makers, APL provider leadership personnel, school leadership personnel, APL teachers and course coordinators, and APL students. Analysis of the documentation and interview data revealed five critical limiting issues of the way APL was promulgated in and through the policy development process: (1) its de-vocationalisation; (2) its under-theorisation; (3) its limited academic recognition; (4) its lack of vocational recognition; and (5) its poor standing. Those issues suggested the importance of the following considerations in APL policy development: a clear and consistent prioritisation of vocational and general education goals; a strongly theory-driven approach; academic credit equivalence into general educational qualifications; the dual recognition of APL in both general secondary and vocational education qualifications; and sensitivity to the unintended consequences of policy developments.